The costume of MoCap: A spatial collision of velcro, avatar and Oskar Schlemmer. Issue 1 (1st October 2014) - Delbridge, Matt
The rationale that governs motion of the organic in the cubical leans towards a transformation of the body in space, emphasizes its mathematical properties and highlights the potential to measure and plot movement – this is the work of a Motion Capture (MoCap) system. The translation in the MoCap studio from physical to virtual is facilitated by the MoCap suit, a device that determines the abstract cubical representation that drives first the neutral, and then the characterized avatar in screen space. The enabling nature of the suit, as apparatus, is a spatial phenomenon informed by Schlemmer's abstract 'native' costume and his vision of the Tanzermensch as the most appropriate form to occupy cubical space. The MoCap suit is similarly native. It bridges the physical and virtual, provides a Victor Turner like threshold and connection between environments, enacting a spatial discourse facilitated by costume. This collision of Velcro, Avatar and Oskar Schlemmer allows a performance of space, binding historical modernity to contemporary practice. This performance of activated space is captured by a costume that endures, in Dorita Hannah's words, despite the human form.